Diseño y construcción de un caldero de 7.5 BHP para generación de vapor. - Córdova Ordóñez, Robert Benigno (2011)
Our research proyect has a main objetive to desing and build a boiler cauldrun, which allows us to observe the transformation processes of the heted energy through the disel`s combustion for the generation of steam, which allows us to apply our knowledge and develop our capacities and abilities, in systems of generation of stearn. Through this research, literature review, methods and materials, results, discussions, conclusions and recommendations. We did a compilation of detailed information of each one the necessary theoretical contents for the development of this research woek, later we planned on adequate desing in based of the math models, as the saine as we asked suggestions to professionals abont the principles and building of pirotubulares caulders. Designed all the constituent parts of the cauldron, made its construction and performance testing. Sheet was developed components of the boiler in the AUTOCAD software, and finally checked with the machine operating the proposed parameters, thus we conclude our thesis project.